Pengaruh Kompensasi dan Pengembangan Karir terhadap Kinerja Pegawai dengan Quality of Work Life (QWL) sebagai Faktor Pemoderasi di PT. Bank BNI Syariah Kantor Cabang Bekasi - Fiqri Surikha (JURNAL CITRA WIDYA EDUKASI, 2018)
This study aims to determine whether the compensation and career paths influence on employee performance of PT Bank BNI Syariah Branch Office Bekasi, either directly or through the Quality of Work Life as an intermediary factor. In this study, which will be tested are: 1) the effect of the Performance Compensation; 2) influence on the Performance Career Development; 3) Compensation influence on performance through Quality of Work Life; and 4) the effect of the Performance Career Development through Quality of work life. In this research approach used is a quantitative approach and the issues to be examined is the problem asosiasif in the form of causal relationships, which relationship is causal. To answer these problems, the researchers chose Path analysis method, this study population were employees of PT Bank BNI Syariah Branch Office Bekasi both contract and permanent employees numbering 100 persons. Researchers used a census collection techniques. The results of this study are concluded that the variable compensation significantly influence employee performance, variable Career Development significantly influence employee performance, compensation to employee performance through variable Quality of Work Life does not need to be done or moderated, career paths on employee performance through variable Quality of Work Life needs to be done or moderated in order to improve employee performance.